2023
DOI: 10.5115/acb.23.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and anatomical importance of foramen magnum and craniocervical junction structures in the perspective of surgical approaches

Abstract: This study was conducted to investigate the clinical and anatomical importance of the relevant region from the perspective of surgical approaches by determining the morphometric analysis of the craniocervical junction and foramen magnum (FM) region and determining their distances from important anatomical points. This research was carried out with 59 skulls found at the Anatomy Laboratories of Erciyes and Ankara Medipol University. Metric measurements of FM and condyle, FM shape, condyle-fossa relationship, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Detailed anatomical studies in different countries have revealed significant variations in the dimensions of the foramen magnum and condyles, emphasizing the need to consider local anatomical peculiarities in neurosurgical interventions. [ 7 ] For instance, analyses in Europe have highlighted variations between genders in foramen magnum measurements,[ 5 , 8 , 9 , 11 , 16 , 23 , 25 , 26 , 38 ] while in Asia, distinct differences between men and women in various cranial measurements have been observed. [ 14 , 18 , 24 , 28 , 31 , 32 , 34 ] These anatomical discrepancies can influence surgical techniques, emphasizing the relevance of an approach tailored to the region and/or geographical area to enhance the outcomes of craniotomies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed anatomical studies in different countries have revealed significant variations in the dimensions of the foramen magnum and condyles, emphasizing the need to consider local anatomical peculiarities in neurosurgical interventions. [ 7 ] For instance, analyses in Europe have highlighted variations between genders in foramen magnum measurements,[ 5 , 8 , 9 , 11 , 16 , 23 , 25 , 26 , 38 ] while in Asia, distinct differences between men and women in various cranial measurements have been observed. [ 14 , 18 , 24 , 28 , 31 , 32 , 34 ] These anatomical discrepancies can influence surgical techniques, emphasizing the relevance of an approach tailored to the region and/or geographical area to enhance the outcomes of craniotomies.…”
Section: Discussionmentioning
confidence: 99%
“…These indices could establish specific parameters for each region, considering the anatomical differences found in detailed anatomical studies. [ 7 , 22 ] By developing customized indices according to geography, surgical techniques could be enhanced, allowing for more precise planning adapted to the unique anatomical characteristics of each population. This personalized approach could reduce risks during cranial interventions, optimizing the effectiveness of procedures and improving postoperative outcomes in neurosurgical surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation